Analyzing trends of Patient Safety Non-Technical Skills among postgraduate trainees through a modified survey tool - Ayesha Abubakar Mitha; Usman Mahboob; Tayyaba Rahman (Journal of the Pakistan Medical Association, 2022)
Objectives: To analyse practices of patient safety non-technical skills among postgraduate trainees to establish the utility of organised teaching programmes in this regard, and to determine the utilisation of different teaching modes. Method: The multicentre, two-phase, cross-sectional study was conducted from February to August 2020 at 27 teaching hospitals across Pakistan which were part of the Patient Safety Friendly Hospital Initiative by the World Health Organisation. The Hospital Survey on Patient Safety Culture was modified with validated additional survey items before using it to gather relevant data. Data was analysed using SPSS 21. Results: In the first phase, 42 additional survey items were developed with content validity ratio >0.66 and item content validity index >0.83. Cronbach’s alpha of the modified survey tool was 0.790. The second phase comprised 388 postgraduate trainees; 199(51.3%) males and 189(48.7%) females. Of them, 134(34.5%) were in the third year of training, 215(55.4%) fourth, and 39(10.1%) in the final year. Highest positive response was found for learning Teamwork 216(55.7%) and the lowest for Situational Awareness 62(15.9%). Leadership had highest good practice responses (subscales range: 77.6% to 76.6%) and Communication had the lowest (subscales range: 16.5% to 74.2%). Agreement on Informal Learning mode was the highest 268(69.1%) and the lowest was for Simulator Learning 63(16.2%). Besides, 274(70.6%) and 281(72.4%) subjects agreed on the supportive role of supervisors and hospital administrations. The correlation of the studied variables with the year of training was significant only for Teamwork (p=0.02) and Medication Safety skills (p=0.01). –Continue